Caroli's Disease Presents as Acute Cholangitis and Recurrent Jaundice: A Case Report - Dr. Mohammed Elamin Elsirag; Dr. Adeel Afzal; Dr. Elfatih Elsiddig Hagelamin; Dr. Mahir Khiralla, (International Journal of Advanced Medical Sciences and Technology (IJAMST), 2026)
Background: Caroli's disease is a rare congenital disorder characterized by dilatation of intrahepatic bile ducts, bile stasis, and bacterial infections. While frequent episodes of cholangitis are common in Caroli's disease, it represents a lifethreatening condition that might lead to sepsis and multi-organ failure if left untreated. The presentation of disease may vary from abdominal pain, cholangitis, or end-stage liver disease; an enlarged liver is usually seen. Caroli's disease is type V in Todani's classification of choledochal cysts, which categorizes them into five types based on their characteristics and anatomical involvement. The Global prevalence was less than 1 in 100,000 births. Male-to-female ratio 1:1.8. Age at diagnosis: Most patients present before age 30. Familial occurrence tends to be sporadic, but familial cases occur in 10-20% of cases. We present a case of Caroli's disease with cholangitis, highlighting the diagnostic approach, clinical course, and treatment strategies. Caroli's disease is often misdiagnosed as uncertain cholestasis until complications like cholangitis occur. ERCP contrast injection can trigger cholangitis in patients with biliary dilatation. We advise limiting ERCP use to therapeutic purposes and employing lowpressure contrast techniques when necessary. Case Presentation: We present a case of a 41-year-old male with a long history of recurrent jaundice and a cholecystectomy 10 years ago, who came to the emergency room with a 6-day complaint of fever, right upper quadrant abdominal pain, and jaundice. Radiological studies showed the characteristic dilation of the bile duct, leading to the diagnosis of Caroli's disease. The patient commenced on fluid resuscitation, IV antibiotics Cefotaxime, and was followed by biliary drainage via stent placed by ERCP, along with administration of ursodeoxycholic acid. Conclusion: This case displays the importance of considering Caroli's disease in the differential diagnosis of patients with recurrent episodes of acute cholangitis.